Advanced refractories for titanium metallurgy based on calcium zirconate with improved thermomechanical properties. Issue 14 (November 2019) - Schafföner, Stefan; Bach, Miriam; Jahn, Constantin; Freitag, Lisa; Aneziris, Christos G.
Abstract: Calcium zirconate refractories exhibit a promisingly high corrosion resistance in contact with titanium alloy melts. In the present article, we improved the thermomechanical properties of calcium zirconate based refractories by altering their microstructure and chemical composition. In a full factorial experimental design we investigated the effects of an insitu phase formation, of the addition of coarse grained MgO aggregates as well as the addition of SrCO3 . Based on these factors, the chemical, physical, mechanical and thermomechanical properties as well as the resulting microstructure were thoroughly characterized. Strikingly, the addition of SrCO3 resulted in significantly improved mechanical properties before and after thermal shock. The improved thermal shock resistance can be attributed to a lower determined thermal expansion coefficient, a homogeneous pore size distribution with a reduced pore size and a better bonding between the matrix and the coarse grained aggregates.